Growing Up Transnational : Identity and Kinship in a Global Era - Schultermandl, Silvia; Friedman, May, 1975- (Book collections on Project MUSE., 2011)
This collection offers a fresh, feminist perspective on family relations, identity politics, and cultural locations in a global era. Using an interdisciplinary approach from fields including gender studies, postcolonial theory, and literary theory, this volume questions the concept of hybridity and the tangible implications of assumed identities. The rich personal narratives of the authors explore hyphenated identities, hybridized families, and the challenges and rewards of lives on and beyond borders. The result is a new transnational sensibility that explores the redefinition of the self, the family, and the nation."--Pub. desc.